Антология выдающихся достижений в науке и технике. Часть 39: Лауреаты Нобелевской премии по физике за 2011-2015 гг. - Баранов, М.И. (Електротехніка і електромеханіка, 2017)
Приведен краткий аналитический обзор выдающихся научных достижений ученых мира, отмеченных Нобелевской премией по физике за период 2011-2015 гг. В число таких достижений вошли открытие ускорения расширения Вселенной, создание прорывных технологий манипулирования квантовыми системами, теоретическое обнаружение механизма происхождения массы субатомных частиц, изобретение энергоэффективных источников света − синих светодиодов и открытие нейтринных осцилляций. Наведено короткий аналітичний огляд основних наукових досягнень вчених світу, які відмічені Нобелівською премією по фізиці за період 2011-2015 рр. До числа таких досягнень увійшли відкриття прискорення розширення Всесвіту, створення проривних технологій маніпулювання квантовими системами, теоретичне виявлення механізму походження маси субатомних частинок, винахід енергоефективних джерел світу − синіх світлодіодів і відкриття осциляцій нейтрино. Purpose. Implementation of brief analytical review of the distinguished scientific achievements of the world scientists-physicists, awarded the Nobel Prize on physics for the period 2011-2015. Methodology. Scientific methods of collection, analysis and analytical treatment of scientific and technical information of world level in area of astrophysics, physics of elementary particles, physics of high energies, of modern theoretical and experimental physics. Results. The brief analytical review of the scientific openings and distinguished achievements of scientists-physicists is resulted in area of modern physical and technical problems which were marked the Nobel Prizes on physics for the period 2011-2015. Originality. Systematization is executed with exposition in the short concentrated form of the known scientific and technical materials, devoted opening of acceleration of expansion of Universe, creation of breach technologies of manipulation the quantum systems, theoretical discovery of mechanism of origin of mass of under-atomic particles, invention of effective power sources of light − blue lightemitting diodes and opening of neutrino oscillations. Practical value. Popularization and deepening of scientific and technical knowledges for students, engineers and technical specialists and research workers in area of modern theoretical and experimental physics, extending their scientific range of interests and cooperation in further development of scientific and technical progress in human society